A symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 Preparation methods and applications of semiconductor materials

Synthesis of symbiotic bismuth-based layered ferroelectric SrBi8Ti7O27 semiconductor material by solvent thermal method solves the problems of high energy consumption and difficult morphology regulation in the existing high-temperature solid-phase synthesis, and achieves efficient synthesis of the material and excellent piezoelectric catalytic performance.

CN116395741BActive Publication Date: 2025-03-25YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310354547.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-03-25
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

The synthesis of existing bismuth-based layered ferroelectric semiconductor materials mostly uses high temperature solid phase methods, which leads to high energy consumption and difficulty in regulating the morphology and microstructure, and cannot effectively improve the specific surface area and active sites of the material, thereby limiting its ferroelectric properties and piezoelectric catalytic properties.

Method used

Solvent Thermal method was used to synthesize symbiotic bismuth-based layered ferroelectric SrBi8Ti7O27 semiconductor material, and materials with large specific surface area and rich active sites were prepared through uniform stirring of stoichiometric ratio, addition of alkali solution, and heating reaction in a hydrothermal kettle.

Benefits of technology

The bismuth-based layered ferroelectric SrBi8Ti7O27 semiconductor materials with strong ferroelectric properties and piezoelectric properties have been synthesized at low cost and low energy consumption, especially in the field of piezoelectric catalysis, which shows the ability to efficiently degrade pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395741B_ABST
    Figure CN116395741B_ABST
Patent Text Reader

Abstract

The invention discloses a symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 The preparation method and application of semiconductor materials include the following steps: step 1, adding bismuth source, SrCl2·6H2O and titanium source into water according to the stoichiometric ratio and stirring evenly; step 2, then pouring alkaline solution into the mixed solution obtained in step 2 and continuing to stir evenly; step 3, then transferring the mixed solution obtained in step 3 into a hydrothermal kettle for heating reaction; step 4, washing and drying the product obtained in step 3, namely, the symbiotic ferroelectric SrBi8Ti7O 27 Semiconductor material. The present invention uses a solvent thermal method to synthesize a bismuth-based layered ferroelectric SrBi8Ti7O with a large specific surface area, abundant active sites, and strong ferroelectric and piezoelectric properties. 27 Semiconductor materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials science, and in particular to a symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 Preparation methods and applications of semiconductor materials. Background Art

[0002] With the rapid development of modern industry and the global economy, excessive discharge of industrial and agricultural wastewater has seriously affected water ecological safety and human health. It is urgent to develop green, environmentally friendly, economical and effective technologies to treat pollutants to reduce pollutant emissions. Semiconductor piezoelectric catalytic technology has been reported to be able to achieve deep degradation and mineralization of low-concentration pollutants, completely decomposing organic pollutants into CO2 and H2O. However, the low mechanical energy conversion efficiency is far from meeting the needs of industrial applications. Therefore, it is of great significance to explore the synthesis of catalysts with efficient piezoelectric catalytic performance.

[0003] In recent years, bismuth-based layered perovskite ferroelectric materials (BLSFs) have been widely studied and reported for their excellent fatigue performance, piezoelectric response and ferroelectric properties. 12 and SrBi4Ti4O 15 It has been reported that they exhibit certain photocatalytic activity and good piezoelectric properties. In order to further improve the piezoelectric catalytic performance of the material, researchers have also proposed many modification methods, such as the regulation of morphology and crystal plane, the construction of defect engineering, the doping / substitution of A and B sites, the formation of a multi-component mixed system solid solution, etc. It is well known that the ferroelectric properties of the material directly affect the piezoelectric properties. Therefore, the ferroelectric properties of the material can be improved by effective means to improve the piezoelectric catalytic performance. It is reported that the use of two different bismuth-based layered structural units to form a new material-symbiotic bismuth-based layered ferroelectric semiconductor can significantly improve the ferroelectric properties of the material. However, the synthesis of bismuth-based layered ferroelectric semiconductors currently mostly uses high-temperature solid-phase methods. The synthesis process is not only energy-intensive, but also often difficult to achieve morphology and microstructure regulation. Therefore, how to use the solvothermal method to synthesize a bismuth-based layered ferroelectric SrBi8Ti7O with a large specific surface area, rich active sites, and strong ferroelectric and piezoelectric properties? 27 Semiconductor materials and their application in the field of piezoelectric catalysis have important research value. Summary of the invention

[0004] The purpose of the present invention is to provide a symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 The preparation method of semiconductor materials uses a solvent thermal method to synthesize bismuth-based layered ferroelectric SrBi8Ti7O with large specific surface area, rich active sites, strong ferroelectric properties and piezoelectric properties. 27 Semiconductor materials.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 A method for preparing a semiconductor material comprises the following steps:

[0007] Step 1, add bismuth source, SrCl2·6H2O and titanium source according to the stoichiometric ratio and stir evenly;

[0008] Step 2, then pour the alkaline solution into the mixed solution obtained in step 2, and continue to stir evenly;

[0009] Step 3, then transferring the mixed solution obtained in step 3 to a hydrothermal kettle for heating reaction;

[0010] Step 4: washing and drying the product obtained from the reaction in step 3 to obtain the symbiotic ferroelectric SrBi8Ti7O 27 Semiconductor materials.

[0011] In step 1, the bismuth source is a bismuth salt, selected from at least one of bismuth nitrate pentahydrate, bismuth sulfate, bismuth chloride, and bismuth citrate, preferably bismuth nitrate pentahydrate.

[0012] In the step 1, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, and titanium tetrachloride, preferably titanium dioxide.

[0013] In step 2, the alkaline solution is selected from at least one of sodium hydroxide and potassium hydroxide, preferably sodium hydroxide; the concentration of the alkaline solution in the entire reaction solution is 3-6 mol / L, preferably 4 mol / L.

[0014] In step 3, the reaction temperature is 180-220° C., preferably 200° C., and the reaction time is 20-30 h, preferably 24 h.

[0015] In step 4, the product is washed with deionized water and centrifuged several times.

[0016] In step 4, drying is performed at 50-70° C. for 12-24 hours, preferably at 60° C. for 12 hours.

[0017] The symbiotic bismuth-based layered ferroelectric SrBi8Ti7O prepared by the above method 27 Semiconductor materials.

[0018] The symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 The application of semiconductor materials as piezoelectric materials in piezoelectric catalysis includes piezoelectric catalytic degradation of pollutants, piezoelectric catalytic production of hydrogen peroxide, piezoelectric catalytic splitting of water to obtain hydrogen and oxygen, and piezoelectric catalytic reduction of carbon dioxide.

[0019] The present invention discloses a symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 Piezoelectric catalysis principle of semiconductor materials:

[0020] Bismuth-based layered ferroelectric SrBi8Ti7O 27 The crystal structure of semiconductor materials (piezoelectric materials) is non-centrosymmetric. When subjected to external stress, mechanical energy can be converted into chemical energy. The specific principle is as follows: Under the action of ultrasound, a large number of cavitation bubbles will be generated in the liquid, and the quenching of cavitation bubbles will produce up to 10 8 Pa pressure and acts on the surface of the piezoelectric material. At this time, piezoelectric potential is generated inside the catalyst, the energy band tilts, and SrBi8Ti7O 27 The carriers inside the material drift continuously along the direction of the electric field, continuously accelerate, and flow toward the bipolar interface of the material, thereby triggering the generation of active oxygen species, causing oxidation-reduction reactions and achieving the degradation of Rhodamine B.

[0021] Beneficial effects:

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The present invention synthesizes the symbiotic bismuth-based layered ferroelectric SrBi8Ti7O by the solvothermal method 27 Semiconductor materials have simple preparation methods, low costs, no need for high-temperature reaction processes and complex reagents, large specific surface area of ​​reactants, rich active sites, and high stability.

[0024] 2. Symbiotic bismuth-based layered ferroelectric SrBi8Ti7O prepared by the present invention 27 The semiconductor material has excellent piezoelectric catalytic performance, especially has high efficient piezoelectric catalytic activity for degrading rhodamine B solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The following are XRD patterns of the ferroelectric materials prepared in the examples and comparative examples.

[0026] Figure 2 The following are SEM images of ferroelectric materials prepared in Examples and Comparative Examples.

[0027] Figure 3 The performance diagram of the ferroelectric materials prepared in the examples and comparative examples in degrading the Rhodamine B solution.

[0028] Figure 4 Flow chart of the preparation method of the embodiment. DETAILED DESCRIPTION

[0029] The present invention will be further explained below in conjunction with the embodiments.

[0030] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0031] The methods are conventional methods unless otherwise specified. The materials are available from public commercial sources unless otherwise specified.

[0032] The following example SrBi8Ti7O 27 And the comparative example Bi4Ti3O 12 、SrBi4Ti4O 15 The performance evaluation method is as follows:

[0033] Bi4Ti3O 12 、SrBi4Ti4O 15 、SrBi8Ti7O 27 Phase evaluation method:

[0034] X-ray diffraction (XRD): The prepared Bi4Ti3O 12 、SrBi4Ti4O 15 、SrBi8Ti7O 27 The crystal structure of the samples was analyzed using a D8Advance series wide-angle X-ray diffractometer from Bruker, Germany, with a scanning speed of 5° / min and a scanning range of 10° to 60°.

[0035] Bi4Ti3O 12 、SrBi4Ti4O 15 、SrBi8Ti7O 27 Microscopic morphology evaluation method:

[0036] Scanning electron microscopy (SEM): The prepared Bi4Ti3O 12 、SrBi4Ti4O 15 、SrBi8Ti7O 27 The materials were tested on a JSM-IT300 series scanning electron microscope of JEOL, Japan, with an acceleration voltage of 5-20 kV.

[0037] Bi4Ti3O 12 、SrBi4Ti4O 15 、SrBi8Ti7O 27 Evaluation method of piezoelectric degradation performance of Rhodamine B:

[0038] SrBi8Ti7O 27Taking piezoelectric degradation of Rhodamine B as an example, the specific process is as follows: first, add 100 ml of 100 mg / L Rhodamine B pollutant into a quartz three-necked flask, and then add 10 mg of symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 Semiconductor materials, the reaction system was placed in a KQ-400DE CNC ultrasonic cleaner, the top stirrer was placed above the three-necked flask, and the catalyst was allowed to fully contact with the pollutant under the dark condition with a stirring speed of 100r / s to achieve adsorption-desorption equilibrium. Then, piezoelectric degradation was carried out under the conditions of a stirring speed of 260r / s and an ultrasonic power of 240W. The 3ml suspension was centrifuged at 3000rmp for 3min to remove the catalyst, and then the concentration of the remaining organic matter was characterized by a UV-1200 liquid ultraviolet spectrophotometer to judge the degradation of the pollutants.

[0039] Bi4Ti3O 12 、SrBi4Ti4O 15 The process of piezoelectric degradation of Rhodamine B is consistent with the above.

[0040] Example Symbiotic Bismuth-Based Layered Ferroelectric SrBi8Ti7O 27 Semiconductor materials and their performance testing

[0041] At room temperature, 3.8806g Bi(NO3)3·5H2O, 0.5591g TiO2, and 0.2666g SrCl2·6H2O were first dispersed in a beaker containing 30mL of deionized water and stirred, then 9.600g NaOH was dissolved in 30mL of deionized water and poured into the above reaction solution and continued to be magnetically stirred, and finally the resulting mixture was transferred to a stainless steel hydrothermal autoclave lined with polytetrafluoroethylene for heating reaction at a temperature of 220°C for 24h. After the reaction, it was washed with deionized water and centrifuged three times, and dried at 60°C for 12h to obtain the symbiotic layered bismuth ferroelectric SrBi8Ti7O 27 Semiconductor materials.

[0042] The piezoelectric catalytic performance of the prepared symbiotic semiconductor material was studied by degrading organic pollutants (RhB) under ultrasonic vibration (70kHz, 260W). 27The semiconductor material was dispersed in 100mL (RhB) pollutant aqueous solution with a concentration of 100mg / L. Stir for 10 minutes in the dark with the ultrasound turned off, and sample every 5 minutes to allow the catalyst and the pollutant to reach adsorption-desorption equilibrium. Then turn on the ultrasound, sample once every 15 minutes, take 4 samples in total, react for 1 hour, and keep the temperature at 25±5℃ during the reaction. The resulting suspension was centrifuged at 3000rmp for 3min to remove the catalyst, and then the concentration of the remaining organic matter was characterized by a UV-1200 liquid ultraviolet spectrophotometer, and the maximum absorption peak absorbance at about 553nm was measured to judge the degradation of the pollutant.

[0043] XRD spectrum Figure 1 As shown;

[0044] SEM images are shown in Figure 2 As shown;

[0045] The degradation rate of Rhodamine B is shown in the figure Figure 3 As shown;

[0046] The specific data are listed in Table 1.

[0047] Comparative Example 1 Preparation of Bismuth-based layered ferroelectric Bi4Ti3O 12 Semiconductor materials and their performance testing

[0048] At room temperature, 3.8806g Bi(NO3)3·5H2O and 0.4792g TiO2 were first dispersed in a beaker containing 30mL of deionized water and stirred, then 9.600g NaOH was dissolved in 30ml of deionized water and poured into the above solution and continued to be magnetically stirred. Finally, the resulting mixture was transferred to a stainless steel hydrothermal autoclave lined with polytetrafluoroethylene. The reaction temperature was 200°C and the reaction time was 24h. After the reaction was completed, it was washed with deionized water and centrifuged three times, and dried at 60°C for 12h to obtain ferroelectric Bi4Ti3O 12 Semiconductor materials.

[0049] The performance test is consistent with the above and will not be repeated here.

[0050] XRD spectrum Figure 1 As shown;

[0051] SEM images are shown in Figure 2 As shown;

[0052] The degradation rate of Rhodamine B is shown in the figure Figure 3 As shown;

[0053] The specific data are listed in Table 1.

[0054] Comparative Example 2 Preparation of Bismuth-Based Layered Ferroelectric SrBi4Ti4O 15 Materials and performance testing

[0055] At room temperature, 3.8806g Bi(NO3)3·5H2O, 0.6389g TiO2, and 0.2666g SrCl2·6H2O were first dispersed in a beaker containing 30mL of deionized water, and then 9.600g NaOH was dissolved in 30mL of deionized water and poured into the above solution and continued to be magnetically stirred. Finally, the resulting mixture was transferred to a stainless steel hydrothermal autoclave lined with polytetrafluoroethylene. The reaction temperature was 220°C and the reaction time was 24h. After the reaction was completed, it was washed with deionized water and centrifuged three times, and dried at 60°C for 12h to obtain ferroelectric SrBi4Ti4O 15 Semiconductor materials.

[0056] The performance test is consistent with that of Example 1.

[0057] XRD spectrum Figure 1 As shown;

[0058] SEM images are shown in Figure 2 As shown;

[0059] The degradation rate of Rhodamine B is shown in the figure Figure 3 As shown;

[0060] The specific data are listed in Table 1.

[0061] for Figure 1 By XRD test of the samples, Example 1, Comparative Example 1 and Comparative Example 2 were respectively 27 、Bi4Ti3O 12 and SrBi4Ti4O 15 The results show that the synthesized catalyst is pure phase without other impurities, which corresponds to the standard cards PDF﹟(35-0795), PDF﹟(43-0973), and PDF﹟(31-1342).

[0062] for Figure 2 Through SEM testing of the samples, it can be found that the three catalysts synthesized by the hydrothermal method are all nano-flower balls formed by stacking of sheet-like nanosheets. The thickness of the samples ranges from about 15 to 50 nm. In addition, it can be clearly seen that SrBi8Ti7O 27 The sheet is larger and thinner, and is more easily deformed under the action of ultrasound of the same frequency, generating a high voltage potential inside. 27 Under the action of the electric field, the internal carriers move in a directed manner toward the bipolar interface of the material, thereby triggering the generation of active oxygen species and achieving the degradation of rhodamine B.

[0063] for Figure 3By testing the piezoelectric degradation performance of Rhodamine B on the samples, it can be seen that after turning on the ultrasonic wave for 60 minutes, SrBi8Ti7O 27 The degradation rate of Rhodamine B was 86.0%; Bi4Ti3O 12 The degradation rate of SrBi4Ti4O 15 The degradation rate was 73.3%.

[0064] The specific data are listed in Table 1.

[0065] Table 1 Degradation rate of ferroelectric materials with a concentration of 100 mg / L Rhodamine B pollutant

[0066] sample Rhodamine B (100 mg / L) degradation rate Example 86.0% Comparative Example 1 53.5% Comparative Example 2 73.3%

[0067] It can be seen from the data in Table 1 that compared with Comparative Examples 1 and 2, the synthesized symbiotic bismuth-based layered ferroelectric SrBi4Ti4O 15 Semiconductor material Example 1 has excellent piezoelectric degradation performance of Rhodamine B.

[0068] It can be seen that the present invention proposes a solvothermal method to synthesize the intergrowth bismuth-based layered ferroelectric SrBi4Ti4O 15 Semiconductor materials have excellent piezoelectric degradation properties.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A symbiotic bismuth-based layered ferroelectric SrBi8Ti7O 27 A method for preparing a semiconductor material, characterized in that: The following steps are involved: Step 1, adding bismuth source, SrCl2·6H2O and titanium source into water according to stoichiometric ratio and stirring evenly; The bismuth source is a bismuth salt selected from at least one of bismuth nitrate pentahydrate, bismuth sulfate, bismuth chloride, and bismuth citrate; the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, and titanium tetrachloride; Step 2, then pouring the alkaline solution into the mixed solution obtained in step 1, and continuing to stir evenly; Wherein, the alkaline solution is selected from at least one of sodium hydroxide and potassium hydroxide, and the concentration of the alkaline solution in the entire reaction solution is 3-6 mol / L; Step 3, then transferring the mixed solution obtained in step 2 to a hydrothermal kettle for heating reaction; The reaction temperature is 180-220 °C and the reaction time is 20-30 h; Step 4: washing and drying the product obtained from the reaction in step 3 to obtain the symbiotic ferroelectric SrBi8Ti7O 27 Semiconductor materials; The product was washed with deionized water and centrifuged several times; and dried at 50-70°C for 12-24 h.

2. The symbiotic bismuth-based layered ferroelectric SrBi8Ti7O prepared by the method of claim 1 27 Semiconductor materials.

3. The symbiotic bismuth-based layered ferroelectric SrBi8Ti7O according to claim 2 27 Application of semiconductor materials as piezoelectric materials in piezoelectric catalytic degradation of rhodamine B.